Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Ikan NilaDi Kecamatan Seginim Kabupaten Bengkulu Selatan - Fithri Mufriantie; Rita Feni; Mizi Pranata (Jurnal Agrisep, 2016)
This study aims to determine the income and factors - factors that affect the income of Tilapia in District Seginim South Bengkulu.This research was conducted in the District Seginim South Bengkulu, the location chosen for the township is central to the production of Tilapia. The method used is a survey method, the method of sampling stratified sampling samples taken Tilapia fish farmers as much as 25% of the population to elect 33 127 samples.The results showed that the average income of Tilapia fish farm in the district of South Bengkulu Seginim amounted Rp.7.465.295, - / period and the cost of feed factor (X3), cost of labor factor (X4) and factors of production (X6) effect highly significant revenue while swimming area (X1), seedlings Cost factors (X2), the price factor (X5) no real effect on revenue.